2018
DOI: 10.1108/rsr-04-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Implementing accessibility initiatives at the Michigan State University Libraries

Abstract: Purpose This paper aims to describe a variety of accessibility initiatives implemented at the Michigan State University (MSU) Libraries to better support persons with disabilities who want to use and access library services and resources. Design/methodology/approach By using two campus accessibility policies to help expand and improve its accessibility efforts, the MSU Libraries implemented accessibility purchasing procedures for e-resources; drafted a five-year accessibility plan, which launched an extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Problems related to IT accessibility cannot be solved by one division, or one department. Techniques that are common for managing digital accessibility on a diverse campus include having a centralized person for coordinating IT accessibility (a champion who is proactive in reaching out to people throughout the university), and the compliance monitoring approaches of procurement, IT accessibility plans, and IT accessibility audits [ 6 , 12 ]. Campus-wide initiatives (such as the Assistive Technology Initiative at George Mason University 3 ), or university system-wide initiatives (such as the California State University Accessible Technology Initiative 4 ), provide some best practices on management structures for coordinating digital accessibility on a campus.…”
Section: Background Literaturementioning
confidence: 99%
“…Problems related to IT accessibility cannot be solved by one division, or one department. Techniques that are common for managing digital accessibility on a diverse campus include having a centralized person for coordinating IT accessibility (a champion who is proactive in reaching out to people throughout the university), and the compliance monitoring approaches of procurement, IT accessibility plans, and IT accessibility audits [ 6 , 12 ]. Campus-wide initiatives (such as the Assistive Technology Initiative at George Mason University 3 ), or university system-wide initiatives (such as the California State University Accessible Technology Initiative 4 ), provide some best practices on management structures for coordinating digital accessibility on a campus.…”
Section: Background Literaturementioning
confidence: 99%
“…By reviewing the 2005–2013 articles, Hendrix et al (2016: 268) concluded that the readers’ attitudes toward e-textbooks were ambivalent: either e-textbook being merely PDF versions of print books or, ironically, its hyperlinks leading to cognitive overload. The review led to the conclusion that people prefer e-books to print for the following three dominant reasons: the convenience and accessibility of e-books and the ability to search across the text (Hendrix et al, 2016) Although accessibility is one of the apparent benefits for the general students, e-textbooks and platforms set up accessibility barriers for students with disabilities (Schroeder, 2018). A systematic literature review studied 17 related papers on e-textbook usability and identified that efficiency, effectiveness, and satisfaction were the dominant usability factors (Wan Noor Azhar and Mustafa, 2019: 12).…”
Section: Literature Reviewmentioning
confidence: 99%
“…"The public library has to balance the voiced demand of a subset of the patronage with the needs of many, increasingly diverse Perpustakaan publik merupakan perpustakaan yang dikelola oleh lembaga pemerintah dan diperuntukkan bagi publik (masyarakat), sehingga semua warga negara dapat mengakses perpustakaan publik (Schroeder, 2018). Mengingat perpustakaan publik bagian dari lembaga pemerintah, maka sistem tata kelola perpustakaan publik dipengaruhi oleh sistem dan peraturan pemerintah.…”
Section: Kajian Budaya Organisasi Perpustakaan Publikunclassified